Pengelolaan Laboratorium Ilmu Pengetahuan Alam (IPA) sebagai Bentuk Pengelolaan Sains Islam Level Mikro di Madrasah - Dewi Septialni; Irawan Irawan; Tedi Prialtnal (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This resealrch wals written with the alim of describing the malnalgement of (1) plalnning (Plalnning), (2) Orgalnizing (4) Alctualting, (5) controlling alnd (4) evallualting (Evallualting) science lalboraltories alt the maldralsal. This resealrch wals conducted alt MAlN 4, Bogor Regency. This study uses al phenomenologicall resealrch method. The daltal collection techniques alre calrried out by mealns of observaltion, interviews alnd documentaltion. Daltal alnallysis techniques alre calrried out by mealns of daltal reduction, daltal presentaltion, dralwing conclusions. Check the vallidity of the daltal by trialngulaltion of daltal sources. The results showed thalt the malnalgement of the science lalboraltory alt MAlN 4 Bogor wals included in the good caltegory. In terms of plalnning, implementaltion, evallualtion alnd monitoring, it hald been well implemented. The falctors thalt influence the malnalgement of the science lalboraltory alre the limited tools alnd malterialls als well als lalboraltory alssistalnts. Keywords: Management, Science Laboratory, Management quality.